2014
DOI: 10.1007/s10096-014-2082-2
|View full text |Cite
|
Sign up to set email alerts
|

Significantly higher occurrence of Cryptosporidium infection in Roma children compared with non-Roma children in Slovakia

Abstract: Cryptosporidiosis is considered to be a widespread world zoonosis. The occurrence of Cryptosporidium species was investigated in Roma children in a district of Eastern Slovakia and, at the same time, also in children of non-Roma parents. In total, 103 children (54 boys and 49 girls) between 0 and 14 years of age were involved in this study. Fifty-three were Roma children and 50 children represented a non-Roma control group. Fecal samples were examined: immunologically [enzyme-linked immunosorbent assay (ELISA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Since then, molecular tools have shown that it has a wide host range, including various mammals (rodents, canids, felids, suids, giraffida, equids, non-human primates and marsupials) and birds (Table 1, Table 2). C. muris is considered a zoonotic species as there have been numerous reports of C. muris in humans and one report in human sewage (Guyot et al., 2001, Gatei et al., 2002, Tiangtip and Jongwutiwes, 2002, Gatei et al., 2003, Palmer et al., 2003, Gatei et al., 2006, Leoni et al., 2006, Muthusamy et al., 2006, Azami et al., 2007, Al Brikan et al., 2008, Neira et al., 2012, Hasajová et al., 2014, Petrincová et al, 2015, Spanakos et al., 2015, Hurkova et al., 2003). …”
Section: Wildlife Associated Outbreaks and Water Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, molecular tools have shown that it has a wide host range, including various mammals (rodents, canids, felids, suids, giraffida, equids, non-human primates and marsupials) and birds (Table 1, Table 2). C. muris is considered a zoonotic species as there have been numerous reports of C. muris in humans and one report in human sewage (Guyot et al., 2001, Gatei et al., 2002, Tiangtip and Jongwutiwes, 2002, Gatei et al., 2003, Palmer et al., 2003, Gatei et al., 2006, Leoni et al., 2006, Muthusamy et al., 2006, Azami et al., 2007, Al Brikan et al., 2008, Neira et al., 2012, Hasajová et al., 2014, Petrincová et al, 2015, Spanakos et al., 2015, Hurkova et al., 2003). …”
Section: Wildlife Associated Outbreaks and Water Contaminationmentioning
confidence: 99%
“…Lucio-Forster et al., 2010) C. andersoni Lindsay et al., 2000 Bos taurus (Cattle)CattleLeoni et al., 2006, Morse et al., 2007, Waldron et al., 2011, Agholi et al., 2013, Jiang et al., 2014, Liu et al., 2014 C. varanii Pavlásek et al., 1995 Varanus prasinus (Emerald Monitor)LizardsNone reported C. baileyi Current et al., 1986 Gallus gallus (Chicken)BirdsNone reported C. parvum Tyzzer, 1912 Bos taurus (Cattle)RuminantsCommonly reported in humans C. meleagridis Slavin, 1955 Meleagris gallopavo (Turkey)Birds and humansCommonly reported in humans C. serpentis Levine, 1980 Elaphe guttata, E. subocularis, Sanzinia madagascarensus (Snakes)Snakes and lizardsNone reported C. felis Iseki, 1979 Felis catis (Cat)CatsMany reports (cf. Lucio-Forster et al., 2010) C. wrairi Vetterling et al., 1971 Cavia porcellus (Guinea pig)Guinea pigsNone reported C. muris Tyzzer, 1907, Tyzzer, 1910 Mus musculus (House mouse)RodentsMany reports – Guyot et al., 2001, Gatei et al., 2002, Tiangtip and Jongwutiwes, 2002, Gatei et al., 2003, Palmer et al., 2003, Gatei et al., 2006, Leoni et al., 2006, Muthusamy et al., 2006, Azami et al., 2007, Al Brikan et al., 2008, Neira et al., 2012, Hasajová et al., 2014, Petrincová et al, 2015, Spanakos et al., 2015…”
Section: Introductionmentioning
confidence: 99%
“…The detailed procedure is listed in the paper by Hasajová et al. . The obtained DNA was stored at −20°C until further processing.…”
Section: Methodsmentioning
confidence: 99%
“…Human infections with C. canis and C. felis have been reported mainly in studies conducted in children in developing countries where they are responsible for as much as 3.3% and 4.4%, respectively, of overall cryptosporidiosis cases . Cryptosporidium muris is also considered a zoonotic species as there have been numerous reports of C. muris in humans and one report in human sewage . In a recent human infectivity study, C. muris was examined in six healthy adults .…”
Section: Zoonotic Cryptosporidium Speciesmentioning
confidence: 99%
“…116 Cryptosporidium muris is also considered a zoonotic species as there have been numerous reports of C. muris in humans and one report in human sewage. [117][118][119][120][121][122][123][124][125][126][127][128][129] In a recent human infectivity study, C. muris was examined in six healthy adults. 130 Volunteers were challenged with 10 5 C. muris oocysts and monitored for 6 weeks for infection and/or illness.…”
Section: Zoonotic Cryptosporidium Speciesmentioning
confidence: 99%